Gambling prevalence and gambling problems amongst land-based-only, online-only and mixed-mode gamblers in Australia: A national study. (July 2022) - Hing, Nerilee; Russell, Alex M.T.; Black, Andrew; Rockloff, Matthew; Browne, Matthew; Rawat, Vijay; Greer, Nancy; Stevens, Matthew; Dowling, Nicki A.; Merkouris, Stephanie; King, Daniel L.; Salonen, Anne H.; et al.
Abstract: This study compared land-based-only gamblers (LBOGs), online-only gamblers (OOGs), and mixed-mode gamblers (MMGs), based on a 2019 Australian national telephone survey ( N = 15, 000). It examined 1) prevalence, demographics and gambling behaviours, 2) problematic gambling, 3) most harmful gambling forms, 4) gambling-related harms-to-self, and 5) risk factors for higher problem gambling severity. Results estimated that 43.1% of Australians were non-gamblers, 39.5% LBOGs, 12.8% MMGs and 4.6% OOGs. MMGs were more likely than LBOGs to be male, younger, unmarried, Australian-born, and indigenous. OOGs were more likely than MMGs to be married, university educated, born outside of Australia, speak a non-English language, and less likely to be indigenous. As hypothesised, MMGs had the highest gambling involvement, gambling problems and gambling-related harm. Relative risk of gambling problems for MMGs (5.1% problem gambling; 11.0% moderate risk gambling), exceeded that of both LBOGs (1.4%; 3.8%) and OOGs (0.7%; 4.7%). Risk factors for problematic gambling included engaging in more gambling forms, being male, single, less educated, indigenous, and speaking a non-English language. Crucially, gambling on the internet (OOGs and MMGs combined) was associated with higher problem gambling severity than land-based-only gambling (LBOGs), even after controlling for these risk factors. The findings can inform targeted public health measures. Highlights: A national study compared land-based-only gamblers (LBOGs), online-only gamblers (OOGs), and mixed-mode gamblers (MMGs). Results estimated that 43.1% of Australians were non-gamblers, 39.5% LBOGs, 12.8% MMGs and 4.6% OOGs. MMGs had the highest gambling involvement, gambling problems and gambling-related harm. Internet gamblers (OOGs, MMGs) had higher problem gambling severity than LBOGs after controlling for gambling involvement.